Playful iconicity: structural markedness underlies the relation between funniness and iconicity. (March 2020) - DINGEMANSE, MARK; THOMPSON, BILL
Abstract : Words like 'waddle', 'flop', and 'zigzag' combine playful connotations with iconic form–meaning resemblances. Here we propose that structural markedness may be a common factor underlying perceptions of playfulness and iconicity. Using collected and estimated lexical ratings covering a total of over 70, 000 English words, we assess the robustness of this association. We identify cues of phonotactic complexity that covary with funniness and iconicity ratings and that, we propose, serve as metacommunicative signals to draw attention to words as playful and performative. To assess the generalisability of the findings we develop a method to estimate lexical ratings from distributional semantics and apply it to a dataset 20 times the size of the original set of human ratings. The method can be used more generally to extend coverage of lexical ratings. We find that it reliably reproduces correlations between funniness and iconicity as well as cues of structural markedness, though it also amplifies biases present in the human ratings. Our study shows that the playful and the poetic are part of the very texture of the lexicon.